The Analysis of Interaction for Center of Economic Growth - Rahmawati, Bella Mayriska; Bowo, Prasetyo Ari (Efficient: Indonesian Journal of Development Economics, 2021)
This study aims to analyze the districts that are the center of economic growth in East Bali; the interaction of the center of economic growth in East Bali with the surrounding areas in the Province of Bali; the position of the economy in each district in East Bali based on the growth rate; base sector and non-base sector in each district in East Bali. This research uses quantitative research. The data used in this research is secondary data. Methods of data analysis using Scalogram Analysis and Marshal Centrality Index; Gravity Analysis; Klassen Typological Analysis; Location Quotient (LQ) analysis. The results showed that Karangasem Regency is the center of economic growth in East Bali and has the strongest interaction with Klungkung Regency, while the weakest interaction is with Jembrana Regency; Karangasem Regency, Klungkung Regency, and Bangli Regency; The agricultural, forestry, and fishery sectors, the mining and quarrying sector, the government administration sector, defense and compulsory social security, and other service sectors are the basic sectors in East Bali. Penelitian ini bertujuan untuk menganalisis kabupaten yang menjadi pusat pertumbuhan ekonomi di Bali Timur; dan nteraksi pusat pertumbuhan ekonomi di Bali Timur dengan daerah sekitarnya di Provinsi Bali; Penelitian ini menggunakan jenis penelitian kuantitatif. Data yang digunakan dalam penelitian ini adalah data sekunder. Metode analisis data menggunakan Analisis Skalogram dan Indeks Sentralitas Marshal; Analisis Gravitasi; Analisis Tipologi Klassen; Analisis Location Quotient (LQ). Hasil penelitian menunjukan bahwa Kabupaten Karangasem merupakan pusat pertumbuhan ekonomi di Bali Timur serta memiliki interaksi yang paling kuat dengan Kabupaten Klungkung, sedangkan interaksi yang paling lemah dengan Kabupaten Jembrana; Kabupaten Karangasem, Kabupaten Klungkung, dan Kabupaten Bangli; Sektor pertanian, kehutanan dan perikanan, sektor pertambangan dan penggalian, sektor administrasi pemerintahan, pertahanan, dan jaminan sosial wajib, dan sektor jasa lainnya merupakan sektor basis di Bali Timur.